Ethical Challenges and Dilemmas in Public Sector Budget Execution: Evidence from Indonesia - Djuni Farhan; Oyong Lisa; Bambang Hermanto (Institut Bisnis dan Informatika Kesatuan, 2026)
This study investigates the ethical conflicts encountered by public sector accountants during budget execution processes, highlighting the implications for governance, accountability, and public trust. The research aims to explore how professional and organizational pressures shape accountants’ ethical decision-making and the extent to which these challenges compromise integrity in public financial management. Using qualitative methods, semi-structured interviews, focus groups, and document analysis, the study examines ethical dilemmas faced by public sector accountants. The study’s findings reveal three main challenges: conflicts of interest, pressure to meet financial targets, and lack of transparency in budget allocation. These are all intensified by political interference, weak ethical cultures, and limited oversight. In performance-driven environments, accountants often compromise professional standards, leading to misreporting, misuse of public resources, and reduced public trust. Applying Rest’s Four-Component Model, the study highlights how organizational culture shapes ethical decision-making. Recommendations include establishing robust codes of conduct, providing ethics education, and strengthening oversight to foster ethical resilience. The ethical conflicts in budget execution undermine credibility, requiring institutional commitment to integrity, transparency, and supportive leadership to ensure public trust and ethical governance.